Philippinozercon, a new genus of Heterozerconidae (Parasitiformes: Mesostigmata), with description of all active instars - Gerdeman, Beverly S.; Garcia, Rufino C.; Herczak, Andrew; Klompen, Hans (Zootaxa, 2018)
The generic classification of millipede associated Heterozerconidae in the Oriental region is revised. The genus Allozercon Vitzthum is re-diagnosed and Asioheterozercon Fain is designated as an subjective junior synonym of Allozercon. Philippinozercon gen. nov., with the type species P. makilingensis sp. nov., is described for all instars. This genus may be endemic for the Philippines, but is quite widespread in that country. All immature instars are described, making this the second species of Heterozerconidae known for all instars. The morphology of the immatures is compared with that of immatures of the temperate species Narceoheterozercon ohioensis and unnamed species from Brazil and Thailand. All immatures were collected from millipede frass and litter, never from millipedes. Adults are associated with millipedes in the family Trigoniulidae (Spirobolida).